Magnitude and associated factors of intraoperative nausea and vomiting among parturients who gave birth with cesarean section under spinal anesthesia at South Gondar zone Hospitals, Ethiopia - Chekol, Basazinew (Ann Med Surg (Lond), 2021)
BACKGROUND: Intraoperative nausea and vomiting are common intraoperative events by which parturient feel discomfort and disturbed after spinal anesthesia. METHODS: Hospital-based cross-sectional study was conducted on mothers who underwent cesarean section with spinal anesthesia. Descriptive analysis and chi-square test were employed. Bivariable and multivariable logistic regressions were used to measure the association of factors with the outcome variable intraoperative nausea and vomiting. A p-value of ≤0.05 was used to decide statistical significance for multivariable logistic regression. RESULT: A total of 246 parturients were participated in this study. The incidence of intraoperative nausea and vomiting was 40.2%. According to multivariable logistic regression, age greater than 30 years (AOR, 6.26; 95%CI, 2.2–17.78; p-value 0.001), primiparous (AOR, 3.72; 95%CI, 1.35–10.24; p-value, 0.011), having motion sickness (AOR, 7.1; 95%CI, 2.75–18.33; p-value 0.001), emergency cesarean sectin (AOR, 9.85; 95%CI, 3.19–30.38; p-value 0.001), oxygen suplimentation (AOR, 0.021; 95%CI, 0.005–0.08; p-value 0.0001) and uterotonic agent (AOR, 2.99; 95%CI 1.24–7.22; p-value 0.015) had statistically significant association with intraoperative nausea and vomiting. CONCLUSION: In our study, the overall incidence of intraoperative nausea and vomiting after spinal anesthesia was 40.2%. Parturients with age greater than 30 years, having motion sickness, didn't get intraoperative supplemental oxygen, oxytocin used for the uterotonic purpose, emergency surgery, and primiparous were at increased risk of intraoperative nausea and vomiting.